2020
DOI: 10.1177/1741143220957328
|View full text |Cite
|
Sign up to set email alerts
|

Establishing professional expectations in further education middle management: The human resource manager’s perspective

Abstract: The further education sector is a challenging working environment with expectations to deliver high-quality education against a backdrop of continuous policy and structural reforms. Further education managers play a key part in how further education institutions respond to this dynamic operating environment. However, despite the importance of this role there is an absence of an agreed set of professional expectations for further education middle managers. Sector bodies have commissioned research to address re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This is a further enhancement compared to Dierdorff et al's ( 2009) and Corbett's (2021) models which had a greater weighting towards hard skills such as technical expertise and knowledge. The high value placed on soft skills in the responses of HR managers previously (Corbett, 2020) and the responses from EMMs in this study highlight the value in a framework that places an emphasis on soft skills. The competencies which make up these skills and traits include:…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…This is a further enhancement compared to Dierdorff et al's ( 2009) and Corbett's (2021) models which had a greater weighting towards hard skills such as technical expertise and knowledge. The high value placed on soft skills in the responses of HR managers previously (Corbett, 2020) and the responses from EMMs in this study highlight the value in a framework that places an emphasis on soft skills. The competencies which make up these skills and traits include:…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, this study found that only 49% of EMMs are in possession of a formal management qualification. Furthermore, when considering Corbett's (2020) study of HR managers' perspective of the FE middle manager role there is a consensus between EMMs responses in this study and HR managers' responses with regard to the priority expectations for an EMM to be effective. Prior research and the findings of this study make evident the competencies required for EMMs to fulfil their role are complex.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations